Analytical Study of Fecal Sample and USG on Prevalence of Complex Inflammatory Bowel Disease (IBD) Along with Effect of Various Therapeutic Agents in Canine Pets of India - Sukanta Biswas, (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2026)
The present analytical study was undertaken to assess the prevalence, diagnosis, and therapeutic management of Complex inflammatory bowel disease (IBD) in canine pets under Indian conditions, conducted between June 2021 and May 2024 at the veterinary clinical complex, WBUAFS, Kolkata and selected private clinics surrounding Kolkata, West Bengal. The study screened 29,733 dogs, of which 3,513 exhibited digestive ailments, and 224 were confirmed IBD cases through hematological, biochemical, and fecal biomarker analyses. Eighteen Labrador Retrievers were selected for detailed therapeutic trials and evaluated using fecal examinations and ultrasonography. The study identified Ancylostoma spp. as the most prevalent helminth, followed by Toxocara and Trichuris species, while Salmonella spp. was the predominant bacterial pathogen. Ultrasonography effectively detected gut wall thickening and loss of layering characteristic of IBD. Therapeutic evaluation revealed that conventional drugs such as prednisolone, tylosin, and metronidazole significantly reduced fecal calprotectin levels, though long-term use was associated with side effects. Conversely, Ayurvedic herbal preparations containing Aegle marmelos, Cyperus rotundus, Punica granatum, and Holarrhena antidysenterica demonstrated comparable or superior efficacy in reducing intestinal inflammation and restoring gut health, without adverse effects. The study concludes that integrating herbal therapies with modern treatment protocols provides a safe, sustainable, and holistic approach for managing canine IBD. These findings contribute valuable insights into diagnostic, epidemiological and therapeutic aspects of IBD, emphasizing the importance of combining traditional and evidence-based veterinary practices for enhanced animal health and welfare.